Translation of Terms of Address from English into Persian: Strategies in Focus - Lotfollahi, Bahareh; Dabbaghi, Azizollah (Mediterranean Journal of Social Sciences, 2012)
This paper investigates the kind of translation strategies and procedures used by translators in the translation of terms ofaddress from English into Persian in three short stories, "The Rocking Horse Winner" by D.H. Lawrence, "A Rose for Emily" by WilliamFaulkner, and "A Little Cloud" by James Joyce. The comparison of terms of address with their translation showed that there is adifference between the system of terms of address in English and Persian. In order to show the kind of relations exist betweeninterlocutors in a more precise manner, translators should avoid a literal translation and pay more attention to cultural elements involvedin the target language.